At Westonci.ca, we provide reliable answers to your questions from a community of experts. Start exploring today! Connect with professionals ready to provide precise answers to your questions on our comprehensive Q&A platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
To solve the given equation, we need to address two parts: finding the restrictions on the variable and solving the equation while keeping these restrictions in mind.
Part a: Finding the restrictions on the variable
The given equation is:
[tex]\[ \frac{9}{7x + 21} = \frac{9}{x + 3} - \frac{6}{7} \][/tex]
First, we need to determine the values of [tex]\(x\)[/tex] that cause the denominators to be zero.
1. For the denominator [tex]\(7x + 21\)[/tex]:
[tex]\[ 7x + 21 = 0 \][/tex]
Solving for [tex]\(x\)[/tex]:
[tex]\[ 7x = -21 \][/tex]
[tex]\[ x = -3 \][/tex]
2. For the denominator [tex]\(x + 3\)[/tex]:
[tex]\[ x + 3 = 0 \][/tex]
Solving for [tex]\(x\)[/tex]:
[tex]\[ x = -3 \][/tex]
So, the value of the variable that makes the denominators zero is [tex]\(x = -3\)[/tex]. This is a restriction on the variable because at [tex]\(x = -3\)[/tex], at least one of the denominators becomes zero, which would make the expression undefined.
Restrictions:
[tex]\[ x = -3 \][/tex]
Part b: Solving the equation
Next, we solve the equation while keeping the restriction [tex]\(x \neq -3\)[/tex] in mind.
The equation to solve is:
[tex]\[ \frac{9}{7x + 21} = \frac{9}{x + 3} - \frac{6}{7} \][/tex]
First, simplify the left-hand side and the right-hand side of the equation.
Left-hand side:
[tex]\[ \frac{9}{7x + 21} \][/tex]
Factor the denominator:
[tex]\[ 7x + 21 = 7(x + 3) \][/tex]
So,
[tex]\[ \frac{9}{7(x + 3)} \][/tex]
Right-hand side:
[tex]\[ \frac{9}{x + 3} - \frac{6}{7} \][/tex]
To solve this equation, let's first eliminate the denominators by finding a common denominator. The common denominator is [tex]\(7(x + 3)\)[/tex].
Multiply every term by this common denominator:
[tex]\[ 7(x + 3) \cdot \frac{9}{7(x + 3)} = 7(x + 3) \cdot \left(\frac{9}{x + 3} - \frac{6}{7}\right) \][/tex]
This simplifies to:
[tex]\[ 9 = 7 \cdot 9 - 6(x + 3) \][/tex]
Simplify the right-hand side:
[tex]\[ 9 = 63 - 6(x + 3) \][/tex]
[tex]\[ 9 = 63 - 6x - 18 \][/tex]
Combine like terms:
[tex]\[ 9 = 45 - 6x \][/tex]
To solve for [tex]\(x\)[/tex], isolate [tex]\(x\)[/tex]:
[tex]\[ 9 - 45 = -6x \][/tex]
[tex]\[ -36 = -6x \][/tex]
[tex]\[ x = 6 \][/tex]
Valid solution:
We must ensure that our solution [tex]\(x = 6\)[/tex] does not violate the restriction [tex]\(x \neq -3\)[/tex]. Since [tex]\(x = 6\)[/tex] is not in the restricted values, it is a valid solution.
Answer:
[tex]\[ x = 6 \][/tex]
Part a: Finding the restrictions on the variable
The given equation is:
[tex]\[ \frac{9}{7x + 21} = \frac{9}{x + 3} - \frac{6}{7} \][/tex]
First, we need to determine the values of [tex]\(x\)[/tex] that cause the denominators to be zero.
1. For the denominator [tex]\(7x + 21\)[/tex]:
[tex]\[ 7x + 21 = 0 \][/tex]
Solving for [tex]\(x\)[/tex]:
[tex]\[ 7x = -21 \][/tex]
[tex]\[ x = -3 \][/tex]
2. For the denominator [tex]\(x + 3\)[/tex]:
[tex]\[ x + 3 = 0 \][/tex]
Solving for [tex]\(x\)[/tex]:
[tex]\[ x = -3 \][/tex]
So, the value of the variable that makes the denominators zero is [tex]\(x = -3\)[/tex]. This is a restriction on the variable because at [tex]\(x = -3\)[/tex], at least one of the denominators becomes zero, which would make the expression undefined.
Restrictions:
[tex]\[ x = -3 \][/tex]
Part b: Solving the equation
Next, we solve the equation while keeping the restriction [tex]\(x \neq -3\)[/tex] in mind.
The equation to solve is:
[tex]\[ \frac{9}{7x + 21} = \frac{9}{x + 3} - \frac{6}{7} \][/tex]
First, simplify the left-hand side and the right-hand side of the equation.
Left-hand side:
[tex]\[ \frac{9}{7x + 21} \][/tex]
Factor the denominator:
[tex]\[ 7x + 21 = 7(x + 3) \][/tex]
So,
[tex]\[ \frac{9}{7(x + 3)} \][/tex]
Right-hand side:
[tex]\[ \frac{9}{x + 3} - \frac{6}{7} \][/tex]
To solve this equation, let's first eliminate the denominators by finding a common denominator. The common denominator is [tex]\(7(x + 3)\)[/tex].
Multiply every term by this common denominator:
[tex]\[ 7(x + 3) \cdot \frac{9}{7(x + 3)} = 7(x + 3) \cdot \left(\frac{9}{x + 3} - \frac{6}{7}\right) \][/tex]
This simplifies to:
[tex]\[ 9 = 7 \cdot 9 - 6(x + 3) \][/tex]
Simplify the right-hand side:
[tex]\[ 9 = 63 - 6(x + 3) \][/tex]
[tex]\[ 9 = 63 - 6x - 18 \][/tex]
Combine like terms:
[tex]\[ 9 = 45 - 6x \][/tex]
To solve for [tex]\(x\)[/tex], isolate [tex]\(x\)[/tex]:
[tex]\[ 9 - 45 = -6x \][/tex]
[tex]\[ -36 = -6x \][/tex]
[tex]\[ x = 6 \][/tex]
Valid solution:
We must ensure that our solution [tex]\(x = 6\)[/tex] does not violate the restriction [tex]\(x \neq -3\)[/tex]. Since [tex]\(x = 6\)[/tex] is not in the restricted values, it is a valid solution.
Answer:
[tex]\[ x = 6 \][/tex]
Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.